Kajian Pengolahan Limbah Cair CPO (Minyak Sawit Mentah) dengan Air Laut dan PAC (Poly Aluminium Chlorida) dalam Menurunkan Kadar Minyak/ Lemak, BOD, COD, TSS dan Menstabilkan Nilai pH - Barus, Linda; Masra, Ferizal (Poltekkes Kemenkes Tanjung Karang, 2022)
Palm Oil Mill Liquid Waste (PMKS) is a potential source of pollution for humans and the environment. PMKS liquid waste generally has a high temperature, is brown, contains dissolved and suspended solids in the form of colloids and high residues of oil, BOD, and COD. If the effluent is not treated first and immediately discharged into the waters, it has the potential to pollute the environment. Previous studies have shown that the comparison value of seawater and liquid waste is 1:3. The highest decrease was 97.3% for BOD, 94.8% for COD, 94.43% for oils and fats, 87.36% for TSS, and a pH of 60.7% with a pH value of 8.5 at a rotation of 60 minutes. The results of this study showed that there was a higher level of pollution reduction. Therefore, in this study, we tried to treat palm oil effluent with seawater and Poly Aluminum Chloride (PAC) and the result is the highest decrease in BOD at 96.21%, COD the highest at 97.5%, the highest oil/fat figure was 48.5%, the highest TSS number 58.0%, the highest pH 13.5%. Suggestions in the CPO liquid waste treatment process should take advantage of the by-product of the anaerobic treatment process that produces methane gas. which can be used to generate electricity. And it can be applied to the initial stage of the CPO liquid waste WWTP which is then processed for the sediment because it contains oil as the raw material for making cream soap.